Error Correction for Laser Tracking System Using Dynamic Weighting Model. (24th December 2013) - Liu, W. L.; Wang, Zhankui; Wang, Shibo; Li, Xiaoyang
Abstract : Laser tracking system (LTS) has been widely used in energy industries to meet increasingly high accuracy requirements. However, its measuring accuracy is highly affected by the dynamic uncertainty errors of LTS, and also the current range and angle measurements of LTS are mainly weighted statically, obtaining the dynamic weighting model which is essential for LTS to improve the measuring accuracy. In this paper, a dynamic weighting model that describes not only the dynamic uncertainty but also the geometric variations of LTS is developed, which can be adjusted to the weighting factors of dynamic parameters according to the range observations relative to the angle observations. Intensive experimental studies are conducted to check validity of the theoretical results. The results show that the measuring accuracy of LTS has been increased 2 times after using this technique for correction.